Khaki-clad Springboks Rugby played by the 6th South African Armoured Division 1943-1946 - Nieman, Gideon (African Sun Media, 2017)
Rugby was played constantly during World War II by service teams. Whenever soldiers met or gathered, sport and games developed. Rugby in the armed forces was often an exuberant reaction from the stern reality of war. It was played with knee-pads on the dusty, gritty sand of the desert and on grass beside the Nile river. This is the story of rugby matches played by the 6th South African Armoured Division in Egypt, Italy and their tour of Europe.